A3.3 Inflammasome is activated in healthy salivary gland epithelial cell lines by necrotic cell debris, whereas it is constitutively active in the epithelial cells of Sjögren's syndrome patients. (31st January 2014) - Vakrakou, A G; Manoussakis, M N
Abstract : Background and Objectives: In our laboratory, recent transcriptome expression analysis of unstimulated cultured non-neoplastic salivary gland epithelial cell lines (SGEC) from Sjögren's syndrome (SS) patients and non-SS controls had indicated the aberrant expression of various inflammatory genes in the SS-SGEC supporting their intrinsic activation status. Additionally, we have recently presented evidence of impaired removal of apoptotic cells and necrotic cell debris (SNEC) in SS patients. Here, we sought to investigate the effect of SNEC in cultured SGEC, as well as the expression of various inflammasome-related genes and proteins in salivary gland tissues and SGEC from SS patients and non-SS controls. Materials and Methods: non-SS SGEC treated with SNEC or apoptotic cells were evaluated for the mRNA and protein expression of various activation markers. In addition, salivary gland (SG) tissues and SGEC from SS patients and non-SS controls were comparatively evaluated for the expression of various inflammasome-related genes and proteins. Results: SGEC treatment (n = 3) with SNEC led to the induction of surface expression of inflammatory molecules, such as ICAM-1, MHC-I, CD86, Fas, TLR-2 (p<0.05). In contrast to SNEC, apoptotic cells did not exhibit such an inflammatory effect, but rather suppressed the inflammatory responsiveness to TLR-3 triggering. SGEC treatment (n = 4) with apoptotic cells ameliorated polyI:C-induced MHC-I expression (35% reduction). SNEC stimulation also upregulated the mRNA levels of IFN-β and PYCARD/ASC in SGEC (6-fold and 4-fold induction at 24-hrs, respectively). Exposure of SGEC to SNEC led to inflammasome activation, as it was indicated by the analysis of SNEC stimulation of LPS-primed SGEC showing the induction of caspase-1 activation (intracellular p20 expression) and IL-1β secretion in the culture supernatant (4.8-fold and 2.5-fold increase, respectively), as well as by speckled ASC formation in immunofluorescence microscopy. Microarray gene profiling and validation analysis in SGEC revealed the aberrant expression of genes involved in the inflammasome signalling in SS-SGEC. Moreover, increased protein expression of IL-1β and ASC was observed in SG tissues of SS patients (5 SS, 5 non-SS). SS-SGEC (n = 9) were also found to secrete constitutively more IL-1β in their culture supernatant, compared to non-SS SGEC (n = 5) (mean ± SE; SS-SGEC: 2.3 pg/ml ± 0.4, non-SS SGEC: 0.8 pg/ml ± 0.3, p = 0.02) likely suggesting the constitutive activation of inflammasome in SS-SGEC cells. Conclusions: These findings indicate that the aberrant exposure of the epithelial cells to necrotic debris may be a major cause of inflammatory reactions via the activation of inflammasome and may hold a key role in the pathogenesis of disorders associated with epithelial activation such as SS.